The Influence of Brand Image, Lifestyle and Word Of Mouth on Maybelline Mascara Purchasing Decisions (Case Study in Environmental Community I Medan Denai) - Safrianti Harahap; Yayuk Yuliana (Lenggogeni Data Publishing, 2024)
This study aims to determine the influence of brand image, lifestyle and word of mouth on the purchase decision of maybelline mascara (case study in the I Medan Denai environmental community). This research is a quantitative research. The data used in this study are primary data obtained through questionnaires, observations and literature studies. The respondents who were sampled in this study amounted to 91 respondents. From the regression equation Y = 16.272 + 0.218X1 + 0.186X2 + 0.114X3 + e. In the partial hypothesis test (t test) the brand image variable has a positive and significant effect on the purchase decision variable with a t-value calculated > t table (6.370 > 1.987) and a significant value of 0.000 < 0.05. Lifestyle variables have a positive and significant effect on purchasing decision variables with t-values calculated > t tables (4.561 > 1.987) and significant values of 0.000 < 0.05. The word of mouth variable has a positive and significant effect on the purchase decision variable with a calculated t value > t table (3.313 > 1.987) and a significant value of 0.001 < 0.05. Brand image, lifestyle and word of mouth variables simultaneously affect purchasing decision variables with F values calculated > F tables (27.268 > 2.71) and significant values 0.000 < 0.05.